ANTUSIASME BELAJAR SISWA PADA PEMBELAJARAN OUTDOR LEARNING MATA PELAJARAN PAI SISWA - Ramadani, Nurhadi Muhammad; Bariyah, Oyoh; Makbul, M (Universitas Islam Madura, 2024)
This research used a quasi-experimental design with a quantitative approach, and the experimental group consisted of 26 students from class VII A. Semi-structured interviews, structured observations, and student interest questionnaires were used to collect data. The research results showed a significant increase in student responses to Outdoor Learning from 69.83% to 84.25%. Statistical analysis revealed an increase in the mean value of learning enthusiasm for the experimental class from 84.04 (pretest) to 91.88 (posttest), while the control class only increased from 85.19 to 89.88. The T-test shows a positive and significant influence (p < 0.05) of Outdoor Learning on enthusiasm for learning, with linear regression analysis indicating a contribution of 48.2%. The N-gain score test shows the effectiveness of this method with a value of 51% for the experimental class compared to 31% for the control class. In conclusion, Outdoor Learning has proven to be effective in increasing enthusiasm for learning PAI through increasing curiosity, social interaction and more challenging learning experiences. This study offers in-depth information for creating more dynamic and engaging teaching strategies for Islamic Religious Education. Research regarding the profile of students' learning enthusiasm in outdoor learning in PAI subjects has very broad implications, both for the world of education, especially Islamic religious education, and for the students themselves. The following are several implications that may be drawn from this research: 1) educational development, 2) learning motivation, 3) awareness of building the future.